A kind of acid-base additive same regulation wide band gap perovskite film and its preparation method and application
Patent Information
- Application Number
- CN202611044603.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-14
- Publication Date
- 2026-10-30
AI Technical Summary
[0003]本发明的目的是针对现有单一钙钛矿添加剂改性效果单一、无协同增益、薄膜缺陷多、器件稳定性差的技术问题,提供一种酸碱添加剂协同调控的宽带隙钙钛矿薄膜及其制备方法和在钙钛矿太阳能电池中的应用,以大幅提升宽带隙钙钛矿薄膜结晶质量与器件光电性能
1. 独创酸碱双组分1+1>2协同增效体系,打破单一改性性能瓶颈;现有技术仅依靠单一组分改性,单一添加剂仅能实现单一维度改性,性能提升幅度低;本发明创新性将酸性对甲苯磺酸水合物与碱性甲基丙烯酸二甲氨基乙酯复配,两组分功能互补、效果放大,薄膜结晶质量、缺陷密度、载流子传输性能、器件光电效率均优于两组分单独改性效果之和,具备协同放大效应;
Smart Images

Figure CN123022104A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of optoelectronic materials technology, specifically relating to the fabrication of wide-bandgap perovskite thin films with synergistic regulation by acid-base additives, their preparation methods, and their application in perovskite solar cells. Background Technology
[0002] Perovskite solar cells, as a next-generation photovoltaic technology, have become a research hotspot due to their high photoelectric conversion efficiency and low-cost fabrication processes. Wide-bandgap perovskite materials have significant application prospects in tandem cells and high-stability photovoltaic modules. However, wide-bandgap perovskite films are prone to problems such as runaway crystallization kinetics, dense grain boundary defects, and insufficient interface stability. These problems seriously affect device efficiency and stability, limiting their practical applications. Existing passivation strategies are mostly based on single-functional additives, which cannot simultaneously solve the problems of crystallization kinetics control and grain boundary passivation. Therefore, it is urgent to develop a multifunctional synergistic additive system to achieve high-quality fabrication of wide-bandgap perovskite films. Summary of the Invention
[0003] The purpose of this invention is to address the technical problems of existing single perovskite additives having limited modification effects, no synergistic gain, numerous film defects, and poor device stability. This invention provides a wide-bandgap perovskite thin film with synergistic regulation by acid and base additives, its preparation method, and its application in perovskite solar cells, so as to significantly improve the crystal quality of wide-bandgap perovskite thin films and the photoelectric performance of devices.
[0004] This invention provides an acid-base synergistic in-situ polymerization additive system, which consists of p-toluenesulfonic acid hydrate (p-TSA·H2O, whose molecular structure is as follows) Figure 1 (as shown) and dimethylaminoethyl methacrylate (DMAEMA, whose molecular structure is as shown) Figure 2 As shown, the components are compounded in a mass ratio of 1:0.5~2, with a preferred mass ratio of 1:1. The modification effect of the two components alone is limited, but the compounding produces a significant synergistic effect, that is, the synergistic effect of 1+1>2 is achieved.
[0005] p-Toluenesulfonic acid hydrate (p-TSA·H2O), as an acidic functional component, achieves a triple function of strong acid regulation, ion passivation, and crystallization control through the sulfonic acid group (-SO3H). Function one involves the uncoordinated Pb in the sulfonic acid group. 2+ First, it forms ion coordination interactions, achieving strong coordination passivation of lead sites; second, it can passivate halogen vacancies in perovskite films, reducing defect state density and suppressing nonradiative recombination of charge carriers; third, it possesses a hydrophobic benzene ring structure, improving the environmental moisture resistance of perovskite films, while the sulfonic acid groups can provide protons (H+). + The acidity of the perovskite precursor solution is adjusted to regulate crystallization kinetics and promote the orderly growth of perovskite crystals.
[0006] Dimethylaminoethyl methacrylate (DMAEMA), as a basic functional component, leverages its tertiary amine group (-N(CH3)2), methacrylic acid double bond (C=C), and ester group (C=O) to achieve three functions: Lewis base coordination, polymerizable network construction, and interface repair. Function 1: The tertiary amine group forms a strong Lewis base coordination with A-site / surface defects in perovskite films, compensating for defects and passivating interface states. Function 2: The methacrylic acid double bond can undergo in-situ polymerization during perovskite crystallization, forming a cross-linked polymer network and constructing a flexible passivation layer. Function 3: The ester group can react with Pb... 2+ Weak coordination occurs, further strengthening the interfacial bonding force and optimizing the charge transport characteristics at the grain boundaries.
[0007] Based on the above-mentioned acid-base synergistic in-situ polymerization additive system, the present invention further provides a method for preparing high-performance wide-bandgap perovskite thin films, specifically comprising the following steps: (1) Preparation of precursor solution: Add wide-bandgap perovskite precursor salt (such as Cs) 0.22 FA 0.78 Pb(I x Br 1-x )3, x=0.7-0.9) were dissolved in a polar mixed solvent of DMF / DMSO with a volume ratio of 4:1 to 7:1 to prepare a perovskite precursor solution with a concentration of 1.2 to 1.8 mol / L. The solution was stirred continuously until the solute was completely dissolved and kept at 60 to 80 °C for later use. (2) Introduction of acid-base synergistic additive: Add the acid-base synergistic in-situ polymerization additive of the present invention, namely p-toluenesulfonic acid hydrate and dimethylaminoethyl methacrylate, to the above perovskite precursor solution and stir thoroughly to obtain a modified precursor solution; wherein, the mass ratio of the two components should be controlled to be 1:(0.5~2), preferably 1:1 ratio. This ratio can achieve the best balance between acid passivation, basic defect compensation and in-situ polymerization protection, and the synergistic effect is optimal. (3) Spin-coating film formation and crystallization control: The modified precursor solution was coated onto a clean substrate (such as an ITO substrate) using spin coating. The first stage spin coating speed was 1000-2000 rpm and the duration was 10-20 s. The second stage spin coating speed was 4000-6000 rpm and the duration was 20-40 s. During the spin coating process, the antisolvent (such as chlorobenzene) was added dropwise at 15-25 s. Subsequently, the film was annealed at 80-120 ℃ for 10-30 min to achieve solution-state nucleation and ordered crystallization of the perovskite film. During this process, p-TSA·H2O and DMAEMA can react with free Pb in the system. 2+ Halogen ions coordinate with each other, regulating the nucleation rate and crystal growth behavior, effectively suppressing disordered growth and grain boundary defect formation; (4) In-situ polymerization of grain boundaries and multidimensional synergistic passivation: During the high-temperature annealing process, the carbon-carbon double bonds of DMAEMA undergo thermally initiated in-situ cross-linking polymerization, which builds a stable cross-linking polymerization network at the perovskite grain boundaries and forms a flexible passivation protective layer. At the same time, the sulfonic acid groups of p-TSA·H2O continuously passivate halogen vacancy defects in the lattice, the tertiary amine groups of DMAEMA continuously compensate for A-site defects and surface defects, and the ester groups further enhance the weak coordination effect at the interface, ultimately obtaining a high-performance wide-bandgap perovskite film with grain boundary passivation, ordered crystallization, low defect density, and excellent environmental stability.
[0008] The entire crystallization process of the modified perovskite film of the present invention was dynamically characterized by in-situ time-resolved spectroscopy. The results showed that the acid-base synergistic modification system of the present invention can regulate the nucleation and growth behavior of perovskite throughout the process. The prepared film has excellent overall uniformity and improved crystallization quality. It can quickly stabilize the wide-bandgap perovskite lattice structure and effectively suppress lattice distortion, disordered grain growth and halogen phase separation.
[0009] Based on the quasi-Fermi level splitting (QFLS) photoelectric performance prediction test, the device corresponding to the preferred ratio modified wide-bandgap perovskite thin film of this invention has a photoelectric conversion efficiency (PCE) of 24.00%, a fill factor (FF) of 0.877, and a short-circuit current density (J / L). SC The value was 20.81 mA / cm. 2 The open-circuit voltage (Voc) is 1.315 V. The core optoelectronic parameter, photoelectric conversion efficiency, is significantly better than that of single p-TSA·H2O modification, single DMAEMA modification, and the blank control group without additives, proving that the acid-base synergistic system of this invention has a significant modification gain effect, which can effectively reduce the charge recombination loss of the device, improve the carrier utilization efficiency, and greatly optimize the photovoltaic output performance.
[0010] The wide-bandgap perovskite thin film prepared by this invention has the advantages of dense crystal structure without pinholes, few lattice defects, excellent carrier transport performance, and strong resistance to moisture and light. It can be used as a high-performance optoelectronic functional material in perovskite solar cells and other optoelectronic devices, and has extremely high practical application value.
[0011] Compared with existing technologies, this invention has the following core innovations and technological advantages: 1. A unique acid-base dual-component synergistic system (1+1>2) breaks through the performance bottleneck of single-component modification; existing technologies rely on single-component modification, and single additives can only achieve single-dimensional modification, resulting in low performance improvement; this invention innovatively combines acidic p-toluenesulfonic acid hydrate with basic dimethylaminoethyl methacrylate, with the two components complementing each other and amplifying the effect. The film crystallization quality, defect density, carrier transport performance, and device photoelectric efficiency are all superior to the sum of the effects of the two components modifying alone, demonstrating a synergistic amplification effect; 2. Achieving precise division of labor among multiple functional groups and simultaneous passivation of multiple types of defects; This invention relies on the specific coordination and reaction characteristics of different functional groups to achieve defect passivation: sulfonic acid groups specifically passivate halogen vacancies and regulate crystallization kinetics; tertiary amine groups and ester groups passivate A-site cation vacancies and film surface defects; in-situ polymerization of carbon-carbon double bonds constructs a grain boundary protection network, solving the technical problem that traditional additives cannot simultaneously passivate lattice defects, interface defects, and grain boundary defects; 3. Achieve dynamic and controllable regulation of the entire perovskite crystallization process; The additive system of this invention plays a continuous role in the entire process of precursor solution regulation, spin-coating nucleation, crystal growth, and annealing crystallization. From the optimization of precursor coordination state and nucleation rate to grain boundary polymerization and crosslinking and in-situ defect repair, the entire process is dynamically regulated, and finally a high-quality wide-bandgap perovskite film with good crystal orientation, stable structure, and excellent optical uniformity is obtained.
[0012] This invention achieves simultaneous crystallization kinetics regulation, multi-dimensional defect passivation, and grain boundary polymerization protection network construction through the synergistic coupling of p-TSA·H2O acidic passivation and DMAEMA alkaline coordination polymerization. This effectively overcomes the technical bottlenecks of existing single-additive modification methods, which have limited effects and cannot simultaneously achieve multi-performance regulation. The cross-linked network and flexible passivation layer formed by in-situ polymerization, combined with the halogen vacancy passivation and hydrophobic effect of p-toluenesulfonic acid hydrate, can significantly reduce film defect density, inhibit ion migration, and improve film structure and environmental stability. Applying this modified film to perovskite solar cells can significantly improve device photoelectric conversion efficiency and long-term service stability, providing a reliable and efficient technical solution for the industrial fabrication of high-performance wide-bandgap perovskite optoelectronic devices. Furthermore, the preparation process of this invention is simple, low-cost, and compatible with existing solution-based mass production systems, making it easy to scale up for industrial production and possessing broad market application prospects. Attached Figure Description
[0013] Figure 1 This is a molecular structure diagram of p-toluenesulfonic acid hydrate (p-TSA·H2O), the additive of this invention.
[0014] Figure 2 This is a molecular structure diagram of dimethylaminoethyl methacrylate (DMAEMA), the additive of this invention.
[0015] Figure 3 This is a schematic diagram of the preparation process of the wide-bandgap perovskite thin film regulated by the acid-base synergistic additive of the present invention.
[0016] Figure 4 This is a schematic diagram of the solar cell device structure based on the modified perovskite thin film of the present invention.
[0017] Figure 5 This is a schematic diagram illustrating the mechanism by which the acid-base synergistic in-situ polymerization additive system of the present invention regulates the wide-bandgap perovskite thin film.
[0018] Figure 6 This is a graph showing the change in absorption peak wavelength over time during the crystallization process of the modified wide-bandgap perovskite of this invention.
[0019] Figure 7 This is a graph showing the change in the half-peak width (WHM) of the absorption peak over time during the crystallization process of the modified wide-bandgap perovskite of this invention.
[0020] Figure 8 This is a graph showing the change in absorption peak intensity over time during the crystallization process of the modified wide-bandgap perovskite of this invention.
[0021] Figure 9 This is a three-dimensional surface diagram of the modified wide-bandgap perovskite thin film of the present invention, showing the time-wavelength-absorbance.
[0022] Figure 10 This is a two-dimensional thermal image of the modified wide-bandgap perovskite thin film of the present invention, representing the time-wavelength-absorbance.
[0023] Figure 11 This is a graph showing the predicted photoelectric conversion efficiency of the modified wide-bandgap perovskite thin film of this invention based on quasi-Fermi level splitting. Detailed Implementation
[0024] The technical solution of the present invention will now be described with reference to the embodiments and accompanying drawings. The listed embodiments are only used to explain the technical content of the present invention and are not intended to limit the scope of protection of the present invention. Example 1
[0025] (1) Preparation of precursor solution: Cs 0.22 FA 0.78 Pb(I 0.85 Br 0.15 3. The perovskite raw material was dissolved in a DMF / DMSO mixed solvent with a volume ratio of 4:1 to prepare a perovskite precursor solution with a concentration of 1.5 mol / L. The solution was placed at 70 ℃ and stirred at a constant temperature until completely dissolved. Then, it was filtered through a 0.22 μm organic filter membrane to remove trace amounts of insoluble impurities and agglomerated particles. After filtration, it was kept at a constant temperature for later use to obtain a stable and homogeneous perovskite precursor mother liquor, thus avoiding film crystallization defects caused by impurities.
[0026] (2) Introduction of acid-base synergistic additive system: Add an acid-base synergistic in-situ polymerization additive system composed of p-toluenesulfonic acid hydrate (p-TSA·H2O) and dimethylaminoethyl methacrylate (DMAEMA) in a mass ratio of 1:1 to the above precursor mother liquor, and continue stirring until the system is uniform to obtain a modified perovskite precursor solution; this ratio can make the acidic passivation component and the alkaline polymerization passivation component functionally complementary, the acidic component passivates halogen defects, and the alkaline component repairs surface / A site defects, so as to achieve synergistic passivation of multiple defects and crystallization kinetics regulation.
[0027] (3) Spin-coating film formation and crystallization control: Clean ITO conductive glass was selected as the substrate and ultrasonically cleaned with acetone, anhydrous ethanol and deionized water for 15 min each, and then treated with ultraviolet ozone for 20 min before use. A two-stage spin-coating process was used to prepare perovskite films: the first stage spin-coating speed was 1000 rpm for 10 s to achieve uniform spreading of the modified precursor solution on the substrate surface and eliminate the problem of uneven film thickness; the second stage spin-coating speed was 4000 rpm for 40 s to achieve rapid film shaping and initial solvent evaporation; chlorobenzene antisolvent was added dropwise at the 25th s of spin-coating to rapidly extract the polar solvent in the system and induce uniform nucleation of perovskite; after spin-coating, the film was immediately placed on a 100 ℃ constant temperature heating table for annealing for 30 minutes. The residual solvent is removed, and the ordered crystallization of perovskite is completed. During this process, p-TSA·H2O and DMAEMA additives can respectively interact with lead ions and halide ions in the system to participate in the regulation of crystallization kinetics, effectively regulate the nucleation and growth rate of perovskite, inhibit the generation of grain boundary defects, and improve the overall crystallization uniformity and density of the film.
[0028] (4) In-situ polymerization of grain boundaries and synergistic passivation of multiple defects: During the high-temperature annealing process, the carbon-carbon double bonds of methacrylic acid in DMAEMA molecules undergo in-situ cross-linking polymerization at the perovskite grain boundaries to form a continuous and dense flexible polymer cross-linking network, which physically blocks water and oxygen erosion and ion migration; at the same time, the sulfonic acid groups of p-TSA·H2O target and passivate the halogen vacancy defects in the perovskite lattice; the tertiary amine groups of DMAEMA compensate for the vacancy at the A site of the perovskite and the surface dangling bond defects, and the ester groups further strengthen the weak coordination with the unsaturated lead sites; through acid-base two-component multifunctional group synergistic passivation and in-situ polymerization modification, a wide-bandgap perovskite functional film with ordered crystal structure, low grain boundary defect density and excellent environmental stability is finally obtained.
[0029] (5) In-situ crystallization kinetics characterization: To verify the regulatory mechanism of the additive of the present invention on the entire crystallization process of perovskite, in-situ time-resolved ultraviolet-visible absorption spectroscopy was performed on the sample. The specific mechanism is as follows: Figure 6The in-situ time-resolved absorption spectrum characteristic peak wavelength evolution curve is used to characterize the dynamic crystallization process of perovskite under the regulation of the acid-base synergistic system of this invention. From 0 to 1 s, the precursor coordination intermediate is formed, and the absorption peak is located in the short wavelength region. From 1 to 10 s, as the solvent continues to evaporate and the crystal nuclei gradually grow, the absorption peak continuously red-shifts, corresponding to the continuous improvement of the perovskite lattice and the continuous participation of additives in coordination modification. After 10 s, the peak wavelength stabilizes around 725 nm without significant shift, proving that the perovskite crystal is fully formed, the lattice structure is stable, and no impurity phases are generated. This result indicates that the acid-base synergistic system of this invention can effectively regulate crystallization behavior, rapidly stabilize the wide-bandgap lattice structure, suppress lattice distortion and phase separation, and ensure the stability of the optical structure of the wide-bandgap perovskite.
[0030] Figure 7 The in-situ time-resolved absorption spectrum half-peak width (HWHM) evolution curve is used to reflect the evolution of film grain uniformity and lattice disorder. Within 0–2 s, the additive rapidly regulates the precursor coordination structure, and the HWHM of the absorption peak narrows rapidly. From 8–12 s, rapid solvent removal and rapid grain growth cause a brief period of size differentiation, resulting in a transient broadening of the HWHM. After 12 s, thanks to the synergistic passivation effect of acid and base and the in-situ crosslinking polymerization effect of DMAEMA, the grain size difference is effectively homogenized, and the HWHM continuously decreases and remains stable at a low level for a long period. This demonstrates that the system of this invention can significantly reduce lattice defects, improve grain uniformity, and obtain high-quality crystalline films.
[0031] Figure 8 The in-situ time-resolved absorption spectrum peak intensity evolution curve is used to dynamically track the entire process of additive coordination reaction, intermediate consumption, and crystal growth. Within 0–2 s, the acid-base dual components rapidly coordinate with lead and halide ions, generating a large number of visible-light-responsive coordination intermediates, and the absorption intensity instantaneously reaches its peak. From 2–10 s, the solvent is rapidly removed, the intermediates are continuously consumed and assembled into perovskite crystal nuclei, and the absorption intensity rapidly decays. After 10 s, the intermediates are basically exhausted, the crystal continues to mature and completes in-situ polymerization and cross-linking, and the absorption intensity tends to stabilize and slightly recover. This result confirms that the acid-base additive of this invention can anchor defects in advance during the solution stage and continuously regulate crystal growth throughout the film formation and crystallization process.
[0032] Figure 9 The three-dimensional surface plot of time-wavelength-absorbance visually illustrates the full-cycle optical evolution of the thin film from precursor coordination, solvent evaporation, crystal nucleation, to crystal formation from 0 to 40 s. From 0 to 15 s, acidic and basic additives rapidly coordinate with perovskite free ions, resulting in a significant high-absorbance region due to the formation of numerous coordination intermediates. After 15 s, as the intermediates are consumed, crystal formation and in-situ polymerization are completed, the absorbance generally decreases and tends to stabilize, indicating stable optical properties of the system. This demonstrates that the acid-base additive synergistic system can participate in the regulation of perovskite crystallization kinetics, effectively suppressing the formation of defects and impurity phases.
[0033] Figure 10 A two-dimensional thermogram of time-wavelength-absorbance is generated, visually presenting the dynamic distribution of the system's absorption intensity over time and wavelength. From 0 to 5 s, acidic and basic additives simultaneously coordinate with free perovskite ions, generating numerous visible-light-active coordination intermediates and rapidly forming a high-brightness coordination intermediate absorption region. From 5 to 15 s, the solvent rapidly evaporates, the intermediates assemble into perovskite nuclei, the intermediate signal gradually fades, and the intrinsic perovskite absorption band undergoes a stable redshift and continues to form. From 15 to 40 s, the coordination intermediates are completely consumed, and the system retains only stable wide-bandgap perovskite characteristic absorption, with no impurity phase absorption tailing in the near-infrared band. This further confirms that the acid-base additive modified system of this invention can effectively suppress halogen phase separation and lattice disorder, obtaining a wide-bandgap perovskite thin film with excellent optical uniformity.
[0034] (6) Quasi-Fermi level splitting (QFLS) test: The performance of the sample is characterized by combining the quasi-Fermi level splitting test with the photoelectric performance prediction model. Figure 11 The graph shows the predicted photoelectric performance results of the quasi-Fermi level splitting, used to verify the effect of the acid-base synergistic additive of this invention on improving the photoelectric performance of the device. The test results are: photoelectric conversion efficiency PCE = 23.998%, fill factor FF = 0.877, and short-circuit current density J... SC =20.809 mA / cm 2 Open circuit voltage V OC =1.315 V. This set of data represents the best performance among all experimental groups. The high open-circuit voltage, high fill factor, and high photoelectric conversion efficiency demonstrate that the thin film has low nonradiative recombination loss, high carrier transport efficiency, and excellent interfacial contact performance. These results indicate that acid-base synergistic in-situ polymerization modification can significantly reduce nonradiative recombination loss, optimize carrier transport capability, and improve the photoelectric output performance of the device, reflecting the synergistic modification advantage of the acid-base synergistic in-situ polymerization system (1+1>2). Example 2
[0035] The only difference between Example 2 and Example 1 is the concentration ratio of p-TSA·H2O to DMAEMA in the additive system. Specifically, p-TSA·H2O and DMAEMA are added to the precursor solution in a mass ratio of 1:2. The remaining preparation process, solvent ratio, spin-coating parameters, annealing conditions, and testing methods remain the same as in Example 1. The modified film of this example showed a photoelectric conversion efficiency of 23.200%, a fill factor of 0.850, and a short-circuit current density of 22.014 mA / cm². 2The open-circuit voltage was 1.239 V. Under this ratio, the film still has good defect passivation and crystallization control capabilities, and its photoelectric performance is better than that of the single additive comparative example and the blank comparative example. However, the open-circuit voltage, fill factor and photoelectric conversion efficiency are lower than those of Example 1, and the overall performance is lower than that of Example 1. Example 3
[0036] The only difference between Example 3 and Example 1 is the concentration ratio of p-TSA·H2O to DMAEMA in the additive system. Specifically, p-TSA·H2O and DMAEMA are added to the precursor solution in a mass ratio of 1:0.5. The remaining preparation process, solvent ratio, spin-coating parameters, annealing conditions, and testing methods remain the same as in Example 1. The modified film of this example showed a photoelectric conversion efficiency of 23.470%, a fill factor of 0.853, and a short-circuit current density of 22.203 mA / cm². 2 The open-circuit voltage is 1.239 V. Under this ratio, the film still has good defect passivation and crystallization control capabilities, and its photoelectric performance is better than that of the single additive comparative example and the blank comparative example. However, the proportion of acidic components is relatively high, which slightly weakens the synergistic effect of crystallization control and interface passivation. The overall photoelectric performance is slightly lower than that of Example 1.
[0037] Comparative Example 1: Modification with single p-TSA·H2O The only difference between Comparative Example 1 and Example 1 is that only 1 mg / ml of p-toluenesulfonic acid hydrate was added, and DMAEMA was not added; the rest of the process was the same as in Example 1. The measured photoelectric conversion efficiency was 22.187%, the fill factor was 0.837, and the short-circuit current density was 21.491 mA / cm². 2 The open-circuit voltage was 1.233V. Although the photoelectric conversion efficiency was slightly better than that of the blank group, it was significantly lower than that of Example 1. The single acidic component can only passivate halogen vacancies to a limited extent, but it cannot repair A-sites and surface defects, nor can it construct a grain boundary polymerization protection network. The film has a high defect density and severe carrier recombination, resulting in limited modification effect.
[0038] Comparative Example 2: Single DMAEMA Modification The only difference between Comparative Example 2 and Example 1 is that only 1 mg / ml of dimethylaminoethyl methacrylate was added, and p-TSA·H2O was not added; the rest of the process was the same as in Example 1. The tested photoelectric conversion efficiency was 22.300%, the fill factor was 0.837, and the short-circuit current density was 21.682 mA / cm². 2 The open-circuit voltage was 1.229 V. The test results showed that although the photoelectric conversion efficiency was better than that of the blank group, it was significantly lower than that of Example 1. The single alkaline component could only achieve limited surface defect modification and could not effectively passivate halogen vacancies or optimize crystallization kinetics. The film crystallization order was poor, and the overall modification effect was significantly weaker than that of the acid-base synergistic system of the present invention.
[0039] Comparative Example 3: Blank Control Group (without any additives) The only difference between Comparative Example 3 and Example 1 is that Comparative Example 3 did not add any additives and used a pure precursor solution to prepare the thin film; the remaining processes were the same as in Example 1. The measured photoelectric conversion efficiency was 21.675%, the fill factor was 0.836, and the short-circuit current density was 21.014 mA / cm². 2 The open-circuit voltage is 1.233 V. Comparative Example 3 has the worst photoelectric conversion efficiency, and the thin film has a large number of lattice vacancies, grain boundary defects and lattice disorder, resulting in the worst crystal quality and photoelectric performance.
[0040] Comparison results between the examples and the comparative examples: The overall performance (photoelectric conversion efficiency) of the perovskite thin films in Examples 2 and 3 was lower than that in Example 1, indicating that the 1:1 mass ratio of p-TSA·H2O to DMAEMA in this invention is the preferred ratio. This ratio allows for simultaneous crystallization kinetics regulation, defect passivation, and in-situ grain boundary polymerization protection, achieving a photoelectric conversion efficiency of 23.998%, the highest among all groups. The photoelectric conversion efficiency of each acid-base compound example was significantly better than that of the single-additive comparative examples and the blank comparative example. The performance improvement far exceeded the simple summation of the individual modification effects of the two components, proving that this invention has a synergistic effect of 1+1>2.
[0041] The above description is only a preferred embodiment of this application. It should be noted that, for those skilled in the art, various forms of improvement and substitution can still be made to the relevant technical solutions based on the technical principles of this application, and these improvements and substitutions should also be considered within the scope of protection of this application.
Claims
1. An acid-base synergistic in-situ polymerization additive system for enhancing the performance of wide-bandgap perovskite thin films, characterized in that, It is composed of p-toluenesulfonic acid hydrate and dimethylaminoethyl methacrylate in a mass ratio of 1:0.5~2; wherein: The p-toluenesulfonic acid hydrate contains sulfonic acid groups, which, as acidic functional components, are used to achieve a triple function of strong acid regulation, ion passivation, and crystallization control: Function 1, the uncoordinated Pb in the sulfonic acid group 2+ Function 1: Forming ion coordination interactions to achieve strong coordination passivation of lead sites; Function 2: Passivating halogen vacancies in perovskite films, reducing defect state density; Function 3: Possessing a hydrophobic benzene ring structure, improving the environmental moisture resistance of perovskite films, while the sulfonic acid group provides protons (H+). + Adjusting the acidity of the perovskite precursor solution regulates crystallization kinetics and promotes the orderly growth of perovskite crystals. The dimethylaminoethyl methacrylate contains tertiary amine groups, methacrylic acid double bonds, and ester groups. As a basic functional component, it performs three functions: Lewis base coordination, polymerizable network construction, and interface repair. Function 1: The tertiary amine groups undergo strong Lewis base coordination with A-site / surface defects in the perovskite film, compensating for defects and passivating interface states. Function 2: The methacrylic acid double bonds undergo in-situ polymerization during perovskite crystallization, forming a cross-linked polymer network and constructing a flexible passivation layer. Function 3: The ester groups interact with Pb... 2+ Weak coordination occurs, which strengthens interfacial bonding and optimizes charge transport characteristics at grain boundaries.
2. A method for preparing a wide-bandgap perovskite thin film with synergistic regulation by acid-base additives, characterized in that, The specific steps of using the acid-base synergistic in-situ polymerization additive system as described in claim 1 are as follows: (1) First, prepare the precursor solution: Dissolve the wide-bandgap perovskite precursor salt in a polar solvent to prepare a perovskite precursor solution with a concentration of 1.2~1.8 mol / L. Stir until completely dissolved and keep warm at 60~80℃ for later use. (2) Introducing acid-base synergistic additives: Add the acid-base synergistic in-situ polymerization additives p-toluenesulfonic acid hydrate and dimethylaminoethyl methacrylate to the above perovskite precursor solution, stir evenly, and obtain a modified precursor solution. (3) Then spin coating film formation and crystallization control: including coating the modified precursor solution on a clean substrate by spin coating, and adding anti-solvent during spin coating; Annealing is then performed to achieve solution-state nucleation and ordered crystallization of the perovskite film; (4) Finally, in-situ polymerization and passivation of grain boundaries are carried out: During the annealing process, the methacrylic acid double bond of dimethylaminoethyl methacrylate undergoes in-situ polymerization at the perovskite grain boundary to form a cross-linked polymerization network and construct a flexible passivation layer. At the same time, the sulfonic acid group of p-toluenesulfonic acid hydrate passivates halogen vacancies, the tertiary amine group of dimethylaminoethyl methacrylate compensates for A-site / surface defects, and the ester group strengthens the weak coordination effect, finally obtaining a wide-bandgap perovskite film with grain boundary passivation, orderly crystallization, and excellent environmental stability.
3. The preparation method according to claim 2, characterized in that, In step (1), the wide-bandgap perovskite precursor salt is Cs. 0.22 FA 0.78 Pb(I x Br 1-x )3, x=0.7-0.9; the polar solvent is a DMF / DMSO mixed solvent with a volume ratio of 4:1 to 7:
1.
4. The preparation method according to claim 2, characterized in that, In step (2), the mass ratio of p-toluenesulfonic acid hydrate to dimethylaminoethyl methacrylate in the perovskite precursor solution is controlled to be 1:(0.5~2).
5. The preparation method according to claim 2, characterized in that, In step (3), the substrate is ITO; the spin-coating modified precursor solution is divided into two stages; the spin-coating parameters for the first stage are 1000~2000 rpm and 10~20 s, and the spin-coating parameters for the second stage are 4000~6000 rpm and 20~40 s; the anti-solvent is added dropwise during the spin-coating process, and the anti-solvent chlorobenzene is added dropwise 15~25 s after the start of spin-coating; the annealing treatment is performed at a temperature of 80~120℃ for a time of 10~30 min.
6. A wide-bandgap perovskite thin film obtained by the preparation method according to any one of claims 2-5.
7. The wide-bandgap perovskite thin film as described in claim 6.
8. The application of the wide-bandgap perovskite thin film of claim 4 as a photoelectric material in the fabrication of optoelectronic devices, characterized in that, The optoelectronic device is a perovskite solar cell.
